Pelatihan Dan Pendampingan Menolam Sebagai Media Dakwah Bagi Pelajar Ponpes Darul Fatah Kecamatan Rumbio Jaya Kabupaten Kampar - Roziah, Roziah; Puspita, Alvi; Ariyanto, Joko; Hermaliza, Hermaliza; Syamsidar, Raja; Sum, T.M.; Nurhidayah, Nurhidayah; Irawan, Bambang; Alisadikin, Muhammad; Herman, Zul (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This Community Service Program aims to train the skills of students at the Darul Fatah Islamic Boarding School, Rumbio Jaya District, Kampar Regency in maintaining traditional folklore in the Kampar language. Another aim of this PkM activity is as a main step in bringing out new talent for penolam in Kampar district, whose presence is dwindling day by day. Apart from that, this training and mentoring is a medium for da'wah for prospective ustadz and ustadzah who are studying at the Islamic boarding school. By having the skill of menolam which is a treasure of the Kampar people, this makes them preachers who have unique values. The implementation of this service is carried out using the training and mentoring approach method or mentorship regularly interactive by presenting someone I don't want a guru as a mentor, namely Mr. Maryulis Terang Bulan. The target of this activity is Islamic boarding school students and also teachers. The results of this community service activity show that 87% of students are interested in menolam. It is hoped that the students' interest will arise in studying nolam further and studying this foklor so that regeneration can be created by pano.